Note [scrap paper] (1942)
1942 038-0026-002 CV WJHPIICFOY IS A SUDDEN IMPROVEMENT IN JAPAN-UNITED STATEE RELATIONS. 10.52 ADD U.S. MARINES. IT IS FELT THAT A BREAKDOWN IN THE PRESENT NEGOTIATIONS IS A POSSIBILITY TO RE RECKONED WITH AND THAT IN SUCH AN EVENT JAPAN WOULD BE LILELY IMMEDIATELY TO DO HER UTMOST TO CRUSH CHIANG KAI CHEK BY ATTACKING THE BURMA ROAD BY WAY OF THAILAND. THIS WOULD PROBABLY BRING JAPAN INTO OPEN CONFLICT WITH GREAT BRITAIN AND PERHAPS WITH THE UNITED STATES ALSO AND WOULD MEAN THE ANNIHILIATION OR CAPTURE OF THE COMPARATIVELY FEW U.S. MARINES IN CHINA. EX TEL CO. M1 . 11 A M UK HO P (FS). 292/946/38/26(II)